'How would an extreme flood have behaved if flood protection works were built?' the case of the disastrous flash flood of November 2017 in Mandra, Attica, Greece. Issue 9 (21st October 2022) - Mitsopoulos, G.; Diakakis, M.; Panagiotatou, E.; Sant, V.; Bloutsos, A.; Lekkas, E.; Baltas, E.; Stamou, A. I.
ABSTRACT: The flash flood in the town of Mandra, Attica, in 2017 that had a return period equal to approximately T = 150 years was one of the most disastrous floods in Greece. Four years later, flood protection works designed for T = 50 years were built. In this work, we pose the research question 'How would this disastrous flood have behaved if flood protection works were built?' To answer this question, we employed the HEC-RAS 1D/2D model, over a detailed DSM, that we calibrated with field measurements to simulate the flood of 2017. We derived the following conclusions: (1) Flooding of the main streets still occurs with 15–25% lower flow velocities and 19–29% lower water depths. (2) The total extent of the inundation areas is reduced by 17%. (3) Works delay flood arrival by approximately 1.5 hour, thus providing the opportunity for an Early Warning System to respond more effectively.